The End of the Cold Loneliness: 3D Comparison between Doto antarctica and a New Sympatric Species of Doto (Heterobranchia: Nudibranchia) - Moles, Juan; Wägele, Heike; Ballesteros, Manuel; Pujals, Álvaro; Uhl, Gabriele; Avila, Conxita (PLOS ONE, 2016)
Although several studies are devoted to determining the diversity of Antarctic heterobranch sea slugs, new species are still being discovered. Among nudibranchs, Doto antarctica Eliot, 1907 is the single species of this genus described from Antarctica hitherto, the type locality being the Ross Sea. Doto antarctica was described mainly using external features. During our Antarctic research on marine benthic invertebrates, we found D. antarctica in the Weddell Sea and Bouvet Island, suggesting a circumpolar distribution. Species affiliation is herein supported by molecular analyses using cytochrome c oxidase subunit I, 16S rRNA, and histone H3 markers. We redescribe D. antarctica using histology, micro-computed tomography (micro-CT), and 3D-reconstruction of the internal organs. Moreover, we describe a new, sympatric species, namely D. carinova Moles, Avila & Wägele n. sp., and provide an anatomical comparison between the two Antarctic Doto species. Egg masses in both species are also described here for the first time. We demonstrate that micro-CT is a useful tool for non-destructive anatomical description of valuable specimens. Furthermore, our high resolution micro-CT data reveal that the central nervous system of both Doto species possesses numerous accessory giant cells, suggested to be neurons herein. In addition, the phylogenetic tree of all Doto species sequenced to date suggests a scenario for the evolution of the reproductive system in this genus: bursa copulatrix seems to have been reduced and the acquisition of a distal connection of the oviduct to the nidamental glands is a synapomorphy of the Antarctic Doto species. Overall, the combination of thorough morphological and anatomical description and molecular analyses provides a comprehensive means to characterize and delineate species, thus suggesting evolutionary scenarios.